KEMAMPUAN PENALARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN METAPHORICAL THINKING DITINJAU DARI DISPOSISI MATEMATIS - Lestari, Indah; Andinny, Yuan (Jurnal Elemen, 2020)
This research aims to know the difference in mathematical reasoning ability learners acquire learning Metaphorical Thinking (MT) and Problem-Based Learning (PBL) in terms of the disposition of Mathematics (high and low). This research was conducted at the Mathematics Education Department of Universitas Indraprasta PGRI. The research design used was the treatment by level 2, with the free variables are both learning MT and PBL, the variable is the ability of mathematical reasoning, and moderator variable was the disposition of mathematics. The research method used is the sample number of experiments with as many as 72 respondents. Data analyzed using a two-way ANOVA test. The results of this research indicate that: (1) there is no influence of the interaction model of learning MT and mathematical reasoning ability against the disposition of mathematics, (2) there is the influence of learning models MT.